COMPARACIÓN DE LAS TÉCNICAS in situ, in vitro Y ENZIMÁTICA (CELULASA) PARA ESTIMAR LA DIGESTIBILIDAD DE FORRAJES EN OVINOS. - Torres G., Giovanna (2009)
The objective of the study was to compare the efficiency of the in situ, in vitro and enzymatic (cellulose) techniques in estimating the digestibility of forage with different nutritional quality in sheep. Samples of three qualities of forage were collected: high (rye grass of 2-4 weeks), medium (rye grass of 8 weeks and alfalfa hay), and low (oat straw). The samples were dried, grounded and passed through 1 mm sieve for the in vitro and cellulose technique and 3 mm sieve for the in situ technique. The in vitro digestibility of dry matter (IVDDM), in situ digestibility of dry matter (ISDDM), and cellulose digestibility of dry matter (CDDM) were determined. Three adult rams with ruminal fistula and fed with a diet based on alfalfa hay and corn stalk. A complete randomized 4 x 3 experimental design (4 quality forages and 3 techniques) was used. The ISDDM was higher (p<0.05) in all forages as compared to IVDDM and CDDM: 91.8 vs 73.9 and 76.5% for high quality forage, 74.2 vs 71.6 and 70.9 for ray grass of 8 weeks and 77.8 vs 68.9 and 68.0 for alfalfa hay, and 34.7 vs 29.5 and 31.7 for low quality forage. None differences were observed between IVDDM and CDDM in forages of medium quality. IVDDM and CDDM values overestimated the quantity of degradable dry matter in high quality forages and underestimated it in medium and low quality forages in relation to ISDDM. It is concluded that there are differences between the in situ, in vitro and cellulose techniques when estimating the digestibility of dry matter forage in sheep, and these difference depend upon the quality of the forage.